How livestock can empower women farmers - ICARDA, Communication Team (International Center for Agricultural Research in the Dry Areas, 2023)
In the Global South, livestock has strong empowerment potential for millions of women by providing protein-rich food for home consumption and sale, strengthening their role as stakeholders.